UPPER CLASS SOCIETY'S PERCEPTION OF MADRASAH AS ACHILDREN'S EDUCATIONPLACE AT MTS ISLAMIYAH BUMI AGUNG LEMPUING - Amma, Tasurun; Syaikhoni, Yusuf; Arif Maspul, Kurniawan (Conciencia, 2024)
This research explores the perceptions of upper-class society towards Madrasah as a place for children's education, focusing on Madrasah Tsanawiyah Islamiyah Bumi Agung in Indonesia. The study aims to identify factors influencing their decisions and how Madrasah can enhance their appeal. Using a qualitative descriptive method, data was collected through interviews with parents from the upper class whose children attend the Madrasah. Secondary data was gathered through literature studies. Thematic analysis was used to identify patterns and themes in the data.The findings reveal that several factors influence the perception of upper-class society towards Madrasah. These include the quality of education, educational facilities, reputation and accreditation, the learning environment, educational costs, extracurricular programs, and socio-cultural factors. Despite public schools offering advantages in educational quality and facilities, upper-class families choose Madrasah for reasons related to religious education, moral values, social environment, and family traditions. Madrasah that maintain and improve these aspects are more likely to attract upper-class students.